PENINGKATAN KETERAMPILAN BERPIKIR KRITIS MELALUI MODEL INKUIRI BERBANTUAN MEDIA KONKRET PADA SISWA KELAS 5 SD NEGERI MANGUNSARI 05 TAHUN PELAJARAN 2018/2019 - Indriyani, Dina; Mawardi, Mawardi; Wardani, Krisma Widi (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
This research aims to improve the critical thinking skills of 5th grade students of SD Negeri Mangunsari 05 in the school year 2018/2019, and to implement the steps of the inquiry learning model in 5th grade. This type of research is classroom action research. To collect the data I use non-technical tests include observation, questionnaires, and documentation. Critical thinking skills in the preliminary study showed that from 40 students there was a percentage of 38% in the very high category, 25% in the high category and 37% in the low category. The result of cycle I showed that 20% are in a very high category, 78% of students occupy a high category and 2% in the low category, while the average skill in the first cycle shows 44.25. In the second cycle there was an increase in the mean score of 47.6 with a very high category presentation of 43%, in the high category there was 57%. Based on the results presented, it prove the use of inquiry learning increase critical thinking skills of 5th grade student of 5th grade of SD Negeri Mangunsari 05 Salatiga